Current Technologies in Vehicular Communication - Dimitrakopoulos, George; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a concise and comprehensive overview of vehicular communication technologies. It classifies all relevant standards, protocols and applications, so as to enable the reader to gain a holistic approach towards the subject of vehicular communications. The primary methods are algorithmic processes and simulation results. First, an overview and classification of vehicular technologies is presented. Then, the book focuses on specific applications of V2V and V2I communications. Special attention is given to recent research and development results regarding R&D projects in the field, in cooperation with car manufacturing companies and universities at a global level. Designed to facilitate understanding of vehicle to vehicle and vehicle to infrastructure technologies, this textbook is appropriate for undergraduate and graduate students of vehicular communications or mobile networks.
Introduction: The History of Vehicular Communications -- Vehicular Communications Standards -- Sustainable Mobility in Smart Cities: Traffic Assessment, Forecasting and Management -- Advanced Driver Assistance Systems (ADAS) -- ICT-Enabled, Knowledge-Based (Cognitive) Management Algorithms for ADAS -- The Future: Towards Autonomous Driving.
Keywords: Telecommunication; Computer networks .; Control engineering; Robotics; Automation; Image processing -- Digital techniques; Computer vision; Communications Engineering, Networks; Computer Communication Networks; Control, Robotics, Automation; Computer Imaging, Vision, Pattern Recognition and Graphics